"A fine old time": feminist print journalism in the 1970s. Issue 1 (2nd January 2017) - O' Brien, Anne
Abstract: In 1970's Ireland, a number of feminist activists became the editors of the women's pages of the national daily newspapers. Their work radically changed women's access to the role of journalist as well as fundamentally altering the normative perspective applied to news stories. These women introduced "new journalism" to Ireland, writing about issues in the private rather than the public sphere and doing so from an explicitly feminist point of view. These female editors inhabited a workspace and culture that was heavily masculine, but they negotiated bias and sometimes outright discrimination in order to change the gendered nature of Irish print media. In so doing, these women offered a new social understanding of women's place in news journalism and in Irish society more broadly.